Pengembangan Modul Ajar Literasi Numerasi Berbasis Problem Based Learning pada Siswa Kelas VII SMP Negeri 3 Palopo - Riskah Riskah; Fahrul Basir; Karmila Karmila; Taufiq Taufiq (Pusat Studi Bahasa dan Publikasi Ilmiah, 2026)
The low level of students' numeracy literacy and the limited availability of contextual teaching materials that encourage active problem-solving highlight the need to develop innovative learning resources aligned with the objectives of the Merdeka Curriculum. This study aims to develop a numeracy literacy teaching module based on Problem Based Learning (PBL) for 7th-grade students at SMP Negeri 3 Palopo, focusing on the topic of data presentation. The study employs a modified 4-D development model (Define, Design, Develop, Disseminate) and was carried out up to the Develop stage. The research subjects consisted of 32 students from class VII B, with instruction conducted over six sessions in April 2026. The results indicate that the module meets the following criteria: (1) valid, with an average validation score of 3.4 (highly valid); (2) practical, with a student response rate of 81% (excellent), an instructional implementation rate of 98.9% (fully implemented), and a student activity rate of 85.4% (highly active); and (3) effective, with an average post-test score of 77.6. The results of this study indicate that the developed PBL-based literacy and numeracy teaching module meets the criteria of being valid, practical, and effective.